A formação de professores e o ensino de Biologia em salas com estudantes surdos - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
The presence of students with deafness has become a reality in regular schools, guaranteed by laws that seek to promote inclusion in our country, requiring an effort from the members of the school, to meet new students who have specific needs in the classroom, such as presence of interpreters and the use of methodologies that favor teaching in the visual field, respecting LIBRAS as the first language. The aim of this work was to identify the methodologies used by biology teachers in genetics classes in rooms that receive deaf students, evaluating their adequacy and relevance. The authors Vygotsky and Paulo Freire, who defend the student as a subject in teaching and learning, emphasize the importance of dialogue in this context. The research locus was five schools in the city of Manaus, and the participants Biology teachers, interpreters and deaf students who answered semi-structured questionnaires and participated in interviews. There were many gaps in the initial training of teachers, and also that their non-formal education may influence their classroom practice. In relation to genetic contents we find potentialities in Mendel's first law, and difficulty related to the second law and the lack of signs in LIBRAS corresponding to scientific terms. Dialogue does not happen between deaf students and teachers and it is difficult between interpreters and teachers, among other things. The participants claimed lack of time. The methodologies used in the room mostly do not prove inclusion through dialogue, but we found differentiated teachers, who promote activities aimed at deaf students, such as seminars, games and other practices in the classroom. Overall, the current classroom setting for deaf students is problematic, partly because of teachers' responsibility, who do not take this diversity of the room as a positive factor and tend not to work together with the interpreters. In part, to the lack of preparation of the school itself as an institution that does not offer necessary materials to the teachers and interpreters, as well as a structure to the deaf student himself who often does not dominate the LIBRAS and does not find support from the school to remedy its gaps. These associated factors create a very different environment from what is expected for inclusion, even though professionals who are trying to change this reality are presented here.
Teacher training and Biology education in rooms with deaf students
Keywords: Ensino de Biologia; Formação de Professores; Práticas Pedagógicas; Educação Inclusiva; Surdez; Teaching of Biology; Teacher training; Pedagogical practices; Inclusive education; Deafness; CIÊNCIAS HUMANAS; CIÊNCIAS BIOLÓGICAS